1994
DOI: 10.3109/00365519409086513
|View full text |Cite
|
Sign up to set email alerts
|

Serum transferrin receptor levels in anaemic patients with rheumatoid arthritis

Abstract: The value of s-Transferrin Receptor (s-TfR) measurements in recognizing simultaneous iron deficiency in anaemia of chronic disease was examined in 35 anaemic patients with active rheumatoid arthritis. Based on a quantification of stainable bone marrow (marrow iron grade 0-4) and serum ferritin concentrations (levels < 60 micrograms l-1) compatible with iron deficiency) the anaemia was found to be aggravated by iron deficiency in 19/35 or 54% of the patients. There was no significant difference between the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
3
21
1
3
Order By: Relevance
“…These ®ndings are contrary to earlier studies which suggested that plasma transferrin receptor was not affected by the anemia of chronic disease (Ferguson et al, 1992;Nielson et al, 1994;Kuvibidila et al, 1996). Further studies are needed to identify additional laboratory indicators of iron de®-ciency anemia in groups of individuals who have a heavy burden of concurrent infection.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…These ®ndings are contrary to earlier studies which suggested that plasma transferrin receptor was not affected by the anemia of chronic disease (Ferguson et al, 1992;Nielson et al, 1994;Kuvibidila et al, 1996). Further studies are needed to identify additional laboratory indicators of iron de®-ciency anemia in groups of individuals who have a heavy burden of concurrent infection.…”
Section: Discussioncontrasting
confidence: 62%
“…Serum or plasma transferrin receptor concentrations are considered a sensitive indicator of tissue iron availability, (Ahluwalia, 1998) and studies have suggested that serum or plasma transferrin receptor is not affected by chronic disease, liver disease, infection, malnutrition or in¯amma-tion (Ferguson et al, 1992;Nielson et al, 1994;Kuvibidila et al, 1996). Serum or plasma transferrin receptor concentrations have been reported to be a sensitive and speci®c marker of iron de®ciency during pregnancy, (Carriaga et al, 1991;A Ê kesson et al, 1998) although this indicator has not been examined widely in populations at high risk for iron de®ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily to serum ferritin, sTfR may thus prove to be a diagnostic test of iron deficiency in patients with inflammation. However, in some studies, sTfR levels could not distinguish accurately among patients with rheumatoid arthritis [92,93], inflammatory bowel disease [94] or other inflammatory disorders [95], those with or without iron deficiency. In addition, several studies have observed higher sTfR levels in iron-replete rheumatoid arthritis patients compared to normal subjects, even if they remain lower than in iron deficiency anemia [92,96 -98].…”
Section: Soluble Tfr and Inflammationmentioning
confidence: 99%
“…In patients with rheumatoid arthritis or other forms of anemia of chronic disorders, sTfR levels may well remain within the normal range even when iron stores are depleted [93] because cytokines or other factors also suppress erythropoiesis directly or through inhibition of Epo production. On the other hand, levels may be elevated even when iron stores are adequate [96] because marrow erythropoietic activity may be increased.…”
Section: Soluble Tfr: a Marker Of Iron Status And/or Erythropoiesis?mentioning
confidence: 99%
“…Die Bedeutung des sTfR zur Diagnostik leerer Eisenspeicher wird kontrovers diskutiert. Einige Studien fanden keinen signifikanten sTfR-Unterschied bei nachweisbarem und nicht nachweisbarem Speichereisen im Knochenmark [38,39], andere fanden dass der sTfR den Eisenmangel bei Frauen anzeigt, wenn dieser als positive Antwort einen Hb-Anstieg nach 3-monatiger Eisentherapie aufzeigt [22]. Der sTfR und Zinkprotoporphyrin zeigten eine gute Vergleichbarkeit und hatten bei Eisenmangel keine erhöhten Werte, aber bei Eisenmangelanämie [40].…”
Section: Bestimmung Von Stfrunclassified